THE USE OF ARABIC AND ENGLISH LANGUAGE IN TAERNID MODERN PESANTREN AL-SYAKIRIN TITI KUNING MEDAN JOHOR - Sukma Wardani, Achyar Zein, Edi Saputra (Pascasarjana UIN Sumatera Utara, 2019)
Abstract: This study uses a qualitative approach. The purpose of this study was to determine theactiveness of santri (students) and the conditions of learning the foreign language (English andArabic) which covers; inhibiting factors, supporting factors and efforts to use foreign languagesat the Modern Islamic Boarding School of Ta’dib Al-Syakirin Titi Kuning Medan Johor. Theresults showed that: 1) Santri (students) are more active using Arabic than English in conversationand learning in Islamic boarding schools. 2) learning and use of the foreign languages at theModern Islamic Boarding School of Ta’dib Al-Syakirin has been implemented since the establishmentof the school until now; 3) supporting factors for foreign language learning are; teacherswho have Islamic boarding schools education background and Middle Eastern graduates (Arabiccountries) and the availability of adequate foreign language learning books. 4) inhibitingfactors are; lack of awareness of students to learn foreign languages well, lack of supporting toolsin foreign language learning, lack of books using English. 5) the efforts made by pesantren inmaximizing foreign language learning, are: procuring foreign language speech contests at least 3months, reward and punishment in the use of foreign languages, the researcher also uses the ‘onehour one word’ method that is effective in learning foreign languagesKeyword: Language and Education Home School